Diabetes Risk Allele of Transcription Factor 7-like 2 (TCF7L2) Polymorphisms is Associated with Higher Glucagon-like Peptide 1 (GLP1) and Lower Insulin Secretion - Saraswati, Made Ratna; Suastika, Ketut; Budhiarta, Anak Agung Gde; Oktavianthi, Suksma; Malik, Safarina G. (The Indonesian Biomedical Journal, 2024)
BACKGROUND: The most influential susceptible gene associated with diabetes, transcription factor 7-like 2 (TCF7L2), has been observed in diverse populations. TCF7L2 influences type 2 diabetes risk through glucagon-like peptide 1 (GLP1) production. The presence of risk allele of TCF7L2 leads to the alteration of gene expression in pancreatic beta cells; however, how the mechanism is related with GLP1 remains unclear. This study was conducted to explore the variations of GLP1 increment and insulin secretion between individuals with and without diabetes risk allele of single nucleotide polymorphisms (SNPs) in TCF7L2.METHODS: A cross-sectional analytic study was conducted involving individuals subjects who harbored known variants of SNPs in the TCF7L2: heterozygote or mutant of rs12255372 (GT or TT), rs7903146 (CT or TT), rs10885406 (AG or GG); as well as control subjects with wild type of rs12255372 (GG), rs7903146 (CC), and rs10885406 (AA). Anthropometric parameters, blood glucose, insulin, and GLP1 were measured; and homeostasis model assessment-beta cell (HOMA-%B) index was calculated.RESULTS: The GLP1 increment response was higher in subjects carrying the diabetes risk allele (0.34±0.80 ng/mL) than those with the wild type (-0.04±0.57 ng/mL) (p=0.041). The HOMA-%B was reduced in subjects carrying the diabetes risk allele (71.64±24.72) than those with the wild type (103.23±68.00) (p=0.011). Among individuals carrying the diabetes risk allele, the likelihood of GLP1 increment with high response was twice as high (p=0.007), while the occurrence of low HOMA-%B was 1.47 more frequent (p=0.011).CONCLUSION: TCF7L2 polymorphisms were associated with the GLP1 increment response and reduced HOMA-%B, which might be potentially contributing to GLP1 resistance in patients with diabetes risk factors.KEYWORDS: diabetes risk, TCF7L2, GLP1, HOMA-%B